Fasting and stimulated glucagon-like peptide-1 exhibit a compensatory adaptive response in diabetes and pre-diabetes states: A multi-ethnic comparative study - Chong, Shiau Chin; Sukor, Norlela; Robert, Sarah Anne; Ng, Kim Fong; Kamaruddin, Nor Azmi (Frontiers in Endocrinology, 2022)
Background Impaired secretion of glucagon-like peptide-1 (GLP-1) among Caucasians contributes to reduced incretin effect in Type 2 diabetes mellitus (T2DM) patients. However, there has been studies emanating from East Asia suggesting preserved GLP-1 levels in diabetes and pre-diabetes (pre-DM). This study aimed to resolve these conflicting findings by investigating the fasting and stimulated total GLP-1 levels during oral glucose tolerance test (OGTT) among Malay, Chinese and Indian ethnicities across the normal glucose tolerance (NGT), pre-DM and T2DM patients. The association between total GLP-1 levels, insulin resistance and insulin sensitivity as well as GLP-1 predictors were also analyzed. Methods A total of 174 subjects were divided into NGT (n=58), pre-DM (n=54) and T2DM (n=62). Plasma total GLP-1 concentrations were measured at 0, 30 and 120 min during a 75 g OGTT. Homeostasis model assessment of insulin resistance (HOMA-IR), HOMA of insulin sensitivity (HOMA-IS) and triglyceride-glucose index (TyG) were calculated. Results Total GLP-1 levels at fasting and 30 min were significantly higher in T2DM compared with pre-DM and NGT. Indians had the highest GLP-1 responses followed by Chinese and Malays. The GLP-1 levels were positively correlated with HOMA-IR and TyG but negatively correlated with HOMA-IS. Indians were the most insulin resistant whereas Chinese were the most insulin sensitive. Ethnicity was a significant determinant of GLP-1 levels with Indians having the strongest positive correlation between GLP-1 and insulin resistance (IR) state. Conclusion This is the first study that showed GLP-1 responses are augmented as IR states increase. Fasting and post OGTT GLP-1 levels are raised in T2DM and pre-DM compared to NGT. This raises a possibility of an adaptive compensatory response that has not been reported before. Among the 3 ethnic groups, the Indians has the highest IR and GLP-1 levels supporting the notion of an adaptive compensatory secretion of GLP-1.